2021
DOI: 10.1155/2021/9350677
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Curative Effect and Prognostic Factors of Radiotherapy for Esophageal Cancer Based on the CNN

Abstract: An esophageal cancer intelligent diagnosis system is developed to improve the recognition rate of esophageal cancer image diagnosis and the efficiency of physicians, as well as to improve the level of esophageal cancer image diagnosis in primary care institutions. In this paper, by collecting medical images related to esophageal cancer over the years, we establish an intelligent diagnosis system based on the convolutional neural network for esophageal cancer images through the steps of data annotation, image p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The largest cluster was “radiomics” (#0) ( 53 56 ), while “tumor segmentation”(#6) ( 57 – 61 )was the earliest research in this field. “Endoscopy” (#9) ( 62 65 ) and “deep learning” (#2) ( 66 70 ) were the latest research hotspots. Figure 7D exhibits the top 25 references with the strongest citation bursts.…”
Section: Resultsmentioning
confidence: 99%
“…The largest cluster was “radiomics” (#0) ( 53 56 ), while “tumor segmentation”(#6) ( 57 – 61 )was the earliest research in this field. “Endoscopy” (#9) ( 62 65 ) and “deep learning” (#2) ( 66 70 ) were the latest research hotspots. Figure 7D exhibits the top 25 references with the strongest citation bursts.…”
Section: Resultsmentioning
confidence: 99%
“…Simple surgical treatment cannot meet the clinical needs of patients with esophageal cancer (43,44). To further enhance the longterm survival rate of patients with esophageal cancer, the implementation of neoadjuvant chemotherapy before surgery attracts extensive attention from medical staff and it shows good therapeutic effects (45). Multiple studies show that neoadjuvant chemotherapy can effectively improve the long-term survival rate of patients with esophageal cancer and alleviate patients' clinical symptoms (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Patients diagnosed with ESCC have a survival rate of fewer than 30 percent after 5 years. Despite the fact that various biomarkers for ESCC have been discovered, the therapeutic relevance of the majority of them has not been validated [ 20 , 21 ]. Therefore, there is an immediate need for research into more effective biomarkers for the diagnosis of ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…Several types of cancers are affected by MMPs in different ways [24,25]. As of this writing, a total of 24 MMPs have been discovered (MMP1, 2, 3, 4, 5,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,23, 23a/23b, 24, 25, 26, 27, and 28). Liu et al reported that lymph node metastases, microvessel density, and an advanced TNM stage were all linked to ESCC patients with elevated MMP1 expression.…”
Section: Discussionmentioning
confidence: 99%